(untitled) (Práxis Educativa, 2024)
This study analyzes the improvement of university teachers of STS (Science, Technology and Society) subjects along the teacher training process, it is based on the perceptions of the classes received by 414 students from the University of Seville. A Likert questionnaire was used with 26 items grouped in pairs, each pair reflecting two opposing teaching approaches: teacher-centred teaching and student-centred teaching, and organised into 3 categories: content, methodology and evaluation. The factorial and descriptive analysis shows changes towards student-centered teaching in the following aspects: working with problems, interactions between content, students’ ideas, and formative and participatory evaluation. It is concluded that the training is promoting improvements in teachers, although partial, and that the questionnaire has been an adequate instrument to obtain the opinions of the students. Keywords: Higher education. Student perceptions. STS Teacher training.